Extending the associations of self-discrepancy beyond general well-being to social relationships: the mediating role of emotions and interpersonal cognition - Lee, Acacia Hui Xian (Nanyang Technological University, 2023)
Self-discrepancy refers to a gap between an individual’s real self and internalised standards for the self and can be assessed from either a personal or relational perspective. Past research on self-discrepancy has demonstrated its negative impact on one’s general well-being but little is known about the associations of self-discrepancy with one’s social relationships. To fill this gap, the main aim of the present research was to advance understanding of self- discrepancy’s associations beyond general well-being to one’s social relationships (i.e., relational well-being). The second aim was to explicate the mechanisms through which self-discrepancy is associated with general and relational well-being. Using a framework of well-being comprising affective, cognitive, and functioning dimensions, four studies were conducted to test the well-being implications of self-discrepancy. Studies 1 and 2 were preliminary investigations of the associations between self-discrepancy and general and relational well-being. Studies 3 and 4 further tested two potential mechanisms through which self-discrepancy could be associated with general and relational well-being, 1) via one’s emotions associated with one’s level of self- discrepancy, and 2) via one’s interpersonal cognition. Results showed that both personal and relational self-discrepancies were associated with poorer general well-being, and this negative association was via higher anger and guilt associated with one’s level of self-discrepancy. On the other hand, relational but not personal self-discrepancy was associated with poorer relational well-being, and this negative association was via lower engagement in perspective taking and higher social self-focused attention. The present research expands on our theoretical understanding of self-discrepancy and hold practical implications for the clinical intervention of self-discrepancy.